2010
DOI: 10.1097/mpg.0b013e3181a4c1d8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Esophageal pH and Multichannel Intraluminal Impedance Testing in Pediatric Patients With Suspected Gastroesophageal Reflux

Abstract: Addition of MII to conventional pH monitoring significantly increases the diagnostic yield in detecting REs, prevalently in infants, and in revealing an association between refluxes and symptoms, prevalently respiratory ones and in infants group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 24 publications
5
62
0
2
Order By: Relevance
“…(8) MII/pH allows us not only to evidence esophageal acid exposure, but also to detect non-acid or weakly acidic reflux events that are prevalent in newborns. (9) It was demonstrated that this technique is able to recognize a higher number of refluxes than traditional pH-metry (10) and it is particularly suitable in newborns, (11) and its application in term and preterm newborns with GERD symptoms has been shown to be safe and well tolerated. (12) MII/pH allows for the observation of some distinctive features of reflux events in these patients, which could influence the corresponding clinical approach.…”
Section: Introductionmentioning
confidence: 99%
“…(8) MII/pH allows us not only to evidence esophageal acid exposure, but also to detect non-acid or weakly acidic reflux events that are prevalent in newborns. (9) It was demonstrated that this technique is able to recognize a higher number of refluxes than traditional pH-metry (10) and it is particularly suitable in newborns, (11) and its application in term and preterm newborns with GERD symptoms has been shown to be safe and well tolerated. (12) MII/pH allows for the observation of some distinctive features of reflux events in these patients, which could influence the corresponding clinical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Because intra or interobserver variability remain relatively high, even among experienced experts, a validated and polished automated analysis is needed for this clinical procedure. This ensures both reliability and reproducibility and significantly decreases the time needed for analysis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that feeding difficulties, chronic pulmonary aspiration, constipation, malnutrition and GER are the major problems in children with CP There are advantages and disadvantages of each method, and the facilities and experience of the center are also important when selecting the test to be used. Esophageal pH-monitoring is one of the most convenient methods but it only recognizes acidic episodes of reflux 12,13,23,24 . A significant proportion of reflux episodes are known to be non-acidic, especially in infants [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal pH-monitoring is one of the most convenient methods but it only recognizes acidic episodes of reflux 12,13,23,24 . A significant proportion of reflux episodes are known to be non-acidic, especially in infants [23][24][25][26][27] . As emphasized in the most recent guidelines, combined multiple intraluminal impedance and pH monitoring (MII-pH) is the most reliable method to evaluate GER 5,10 .…”
Section: Discussionmentioning
confidence: 99%